Increasing Physical Tolerance during Cardiac Rehabilitation Helps to Restore Endothelial Function in Patients after Acute Coronary Syndrome - Nataliia M. Tereshchenko; Yuliia Yu. Kovalchuk; Valentyn O. Shumakov; Iryna E. Malynovska; Liana M. Babii (Ukrainian Journal of Cardiovascular Surgery, 2023)
In recent years, many studies have been aimed at exploring the possibilities of cardiac rehabilitation as a tool to improve the prognosis in patients after acute coronary syndrome (ACS). Endothelial dysfunction is one of the initiating mechanisms of cardiovascular diseases, and myocardial infarction in particular, so it is important to assess the dynamics of changes in the number of endothelial progenitor cells (EPCs) in patients during cardiac rehabilitation with the increase in physical activity.The aim. To establish the relationship between the level of recovery of exercise tolerance and the recovery of endothelial function by determining the number of EPCs in patients undergoing cardiac rehabilitation after ACS.Materials and methods. The study included 44 patients with ST-elevation myocardial infarction who underwent urgent stenting of the infarct-related artery, with a mean age of 59 years (Q1-Q3; 51-64). All the study participants underwent laboratory tests (CD45+/CD34+ cell count before and after the exercise test) and instrumental tests (echocardiography, bicycle ergometry, coronary angiography). Statistical processing was carried out using SPSS Statistics 23 (trial version).Results. According to the results of the exercise test at the first examination, the patients were divided into 2 groups: group 1 with low exercise tolerance (≤50 W) and group 2 with high exercise tolerance (>50 W). The data obtained indicate a link between better recovery of exercise tolerance after ACS and recovery of endothelial func-tion in patients with high exercise tolerance during follow-up compared to the patients whose exercise tolerance did not exceed 50 W, as evidenced by a statistically higher number of EPCs after exercise in patients with a favor-able course and high exercise tolerance (3633 vs. 2400 cells/ml) (p=0.006). Patients with low exercise tolerance were more likely to be diagnosed with lesions of left anterior descending coronary artery (96% vs. 70%, p=0.02). More severe coronary vascular lesions with stenosis of 75% of two or more arteries showed lower pre-exercise EPCs, but increased post-exercise EPCs (+228 cells/ml), whereas in the group with stenosis of more than 75% of one vessel, a decrease in post-exercise EPCs (–604 cells/ml) was observed (p=0.004). If patients have more than one stent, there is a 2.5-fold increased risk of decreased exercise tolerance to values of 25-50 W (relative risk = 1.8; 95% confidence interval: 1.3-2.4).Conclusions. The data obtained indicate that there is an association between a better recovery of exercise tolerance after ACS and recovery of endothelial function in patients with a favorable course at repeated examination, compared to patients whose level of exercise tolerance did not exceed 50 W (low exercise tolerance), as evidenced by a statistically greater number of EPCs after exercise test in patients with favorable course and high exercise tolerance compared with patients with unfavorable course and low exercise tolerance.